Effect of Iron and Folic Acid Supplementation on the Infants Birth Weight: A Meta-Analysis - Atiqoh Khoirunnisa' Maftuch; Bhisma Murti; Setyo Sri Rahardjo; Ika Sumiyarsi Sukamto; Revi Gama Hatta Novika (Masters Program in Public Health, Universitas Sebelas Maret, Indonesia, 2025)
Background: Low birth weight (LBW), defined as a birth weight of less than 2,500 grams, is associated with an increased risk of neonatal mortality and developmental disorders. Efforts to prevent and manage LBW can be made through the administration of iron and folic acid supplements during pregnancy. This study aims to estimate and analyze the effect of iron and folic acid supplementation on the birth of infants with low birth weight. Subjects and Method: This study is a systematic review and meta-analysis of relevant previous studies conducted using the PRISMA guidelines. The population included pregnant women, interventions involving iron and folic acid supplementation compared to no supplementation, and outcomes related to low birth weight. Article searches were conducted in the PubMed, ScienceDirect, Scopus, and Google Scholar databases, published between 2013 and 2025. The search terms were (